THE EXISTENCE OF TRADITIONAL SUNDANESE CHILDREN’S FOLK SONG AS NURSERY RHYMES AMONGST PARENTS IN WEST JAVA - Annisa, Yulia Nur; Lismarina, Lilis; Sa'diyah, Siti Aisyah; Badzlina, Elnaeni (Universitas Al-Hikmah Indonesia, 2024)
This study aims to investigate the existence of traditional Sundanese children's songs (folk song) as nursery rhymes in parenting practices, using a survey research method with a cross-sectional study design. The population of this study consists of parents in West Java, with a sample of 340 parents from 18 districts and 8 cities in the region. The samples include three groups of parents: early adults, middle adults, and elderly (under the age of 40, 41-59, and over 60), who were selected using random sampling techniques. The findings show a lack of the existence of Sundanese traditional children's songs as nursery rhymes among parents in West Java, with an average score of 62.76%. The level of knowledge among parents in West Java indicates that around 77.18% of them have an understanding of the cultural values and Sundanese songs. However, the incorporation of cultural values through the use of traditional Sundanese children's songs in parenting is still limited, with an average score of 64.07%. This reflects the limited experience of parents singing or introducing these songs, leading to a lack of memorable connections to Sundanese songs among previous generations. Many parents rarely sing these songs to their children or grandchildren, and a significant portion does not believe that there is any connection between Sundanese songs and parenting. The frequency of parents using Sundanese children's songs in daily parenting activities shows an average score of about 47.15%, indicating a lack of parental involvement in incorporating these traditional songs into everyday parenting practices. This includes singing songs, using them to lull children to sleep, during play, or even to calm children when they are upset or crying.